2005
DOI: 10.1038/oby.2005.74
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Adiponectin Expression in Human Adipocytes: Effects of Adiposity, Glucocorticoids, and Tumor Necrosis Factor α

Abstract: Objective: Adiponectin mRNA expression in isolated subcutaneous and omental adipocytes was examined across a wide range of adiposity to determine whether adiponectin synthesis is impaired in these adipose tissue depots in obese humans. Tumor necrosis factor (TNF)␣ and dexamethasone were tested for inhibitory effects on adiponectin release from human adipocytes in vitro. Research Methods and Procedures: Adipocytes were isolated by collagenase digestion of abdominal adipose tissue obtained from subjects undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
5
20

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(146 citation statements)
references
References 47 publications
9
112
5
20
Order By: Relevance
“…The mechanisms underlying social-defeat-induced reduction in circulating adiponectin levels are not yet known. However, studies have shown that glucocorticoid stress hormones inhibit adiponectin gene expression and secretion both in vitro and in vivo (39)(40)(41)(42). It seems reasonable to speculate that social-defeat-induced decrease in plasma adiponectin levels may be attributed to stress-induced glucocorticoid surge.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanisms underlying social-defeat-induced reduction in circulating adiponectin levels are not yet known. However, studies have shown that glucocorticoid stress hormones inhibit adiponectin gene expression and secretion both in vitro and in vivo (39)(40)(41)(42). It seems reasonable to speculate that social-defeat-induced decrease in plasma adiponectin levels may be attributed to stress-induced glucocorticoid surge.…”
Section: Discussionmentioning
confidence: 97%
“…31 Kern et al 30 found a similar negative relationship between TNFa release and adiponectin release by human adipose tissue in vitro. 30 While TNFa is a potent inhibitor of adiponectin release by murine 3T3-L1 adipocytes, 32,33 it inhibited adiponectin release by only 7% in human adipocytes. 32 However, Wang and Trayhurn 34 reported a decrease due to TNFa of adiponectin mRNA in human The values are the means of 8 experiments using fractions derived from omental adipose tissue from as many women.…”
Section: Discussionmentioning
confidence: 99%
“…A c/EBP-α consensus binding site has been found in the first intron of the gene but functional significance for regulation is not yet established [32]. Glucocorticoids, TNF-α or IL-6 are putative negative regulatory factors of the adiponectin gene whereas insulin-mediated regulation has not been documented [33,34]. This may be surprising in view of the observation that insulin is able to suppress the concentra- Results are means±SD of ten subjects studied longitudinally before and during pregnancy.…”
Section: Regulation Of Adiponectin Expressionmentioning
confidence: 99%